Maternal effects and settlement performance of the green crab Carcinus maenas - Eiras, Felisa Rey (2018)
The majority of benthic marine invertebrates display complex life cycles characterized by life stages with contrasting features. These organisms commonly exhibit a dispersive pelagic larval form(s) that experiences a dramatic event that shifts its morphology and behaviour – the metamorphosis. This event gives origin to a benthic juvenile stage that may also experience additional changes in its morphology, behaviour and physiology until reaching the adult stage and becoming sexually mature. The path between hatching and settlement is a challenging one that only a minute fraction of individuals overcomes. Unravelling the processes that condition the life history strategies and settlement success of benthic marine invertebrates is essential to understand the shaping of adult populations, as well as ecological and evolutionary pathways. In this regard, the present thesis analyses important stages in the life history of a model benthic marine invertebrate with a complex life cycle: the embryonic development, larval settlement and early benthic performance of the green crab Carcinus maenas. The first part of this thesis analyses maternal effects as a source of variability in offspring quality, using biochemical tools. It explores the hypothetical existence of embryonic variability as a consequence of their positioning within the brooding chamber at oviposition and during embryogenesis. Fatty acid profiles of embryos in early (stage 1) and late (stage 3) stages are used as proxies to analyse maternal provisioning and larval quality at hatching, respectively. Through a lipidomic approach, the embryogenesis of C. maenas and Necora puber, two closely related brachyuran crabs that occur in sympatry in the study site, is compared. Polar lipid dynamics is unravelled for the first time in these ecologically and economically important species. Finally, two different time scales, annual and seasonal, are employed to investigate the existence of temporal variability in offspring quality, with the role that maternal size may play as another source of variability also being investigated. The second part of this thesis focus in the early benthic life of juvenile C. maenas. Wild megalopae collected in Ria de Aveiro are used to understand how the pelagic life experienced by developing larvae before becoming competent (receptive to settlement cues) can condition their early benthic life. Competent larvae are exposed to extreme abiotic and trophic conditions to comprehend how their phenotypic plasticity and potential carry-over effects influence consecutive life stages. The part of the study addressing maternal effects revealed that C. maenas did not present any significant within brood variability in newly extruded (stage 1) and ready to hatch (stage 3) embryos. Therefore, maternal provisioning and the incubation environment within the brooding chamber were homogeneous across the whole brood. Nevertheless, a highresolution lipidomic analysis showed that embryogenesis is a dynamic process, suggesting a specialization of lipid functions along the embryonic development. Moreover, maternal provisioning and incubation environment were not influenced by maternal size. Nonetheless, the lipid composition of the yolk was conditioned by the period in which the ovarian maturation occurred. While the environmental conditions prevailing during the incubation altered the fatty acid profile of the ready to hatch embryos. After experiencing a planktonic life, competent larvae displayed different post-settlement performance, clearly reflecting the pelagic conditions that they have experienced during their larval life. Optimal grow-out conditions did not delete these larval fingerprints, with their consequences being carried-over to early benthic life and conditioning the phenotype of juvenile crabs. Larval life plays such an important role in the life history of benthic marine invertebrates that even exposure during a few days to extreme abiotic and trophic conditions can influence their post-settlement performance. Overall, metamorphosis is definitely not a new beginning for C. maenas. In fact, the early postmetamorphosis performance of this brachyuran crab can be strongly conditioned by trait mediated effects that are carried over from its embryonic and/or pelagic larval life to its benthic juvenile and/or adult stages.